2015
DOI: 10.1021/acs.jpcc.5b07516
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Dipolar Interactions in Fe3–xO4 Nanoparticles

Abstract: A general method for the quantification of dipolar interactions in assemblies of nanoparticles has been developed from a model sample constituted by magnetite nanoparticles of 5 nm in diameter, in powder form with oleic acid as a surfactant so that the particles were solely separated from each other through an organic layer of about 1 nm in thickness. This quantification is based on the comparison of the distribution of energy barriers for magnetization reversal obtained from time-dependent relaxation measurem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…The M s value is in agreement with the measured value whereas the K eff value is in good agreement with the reported value for bulk magnetite29. Differences between the experimental and calculated FC curves could be assigned to the occurrence of particle-particle interaction, once the effect of those interactions is the flattening of the FC curves, in agreement with the literature30. In the low temperature region the blocking temperature distribution has been assigned mainly to the contribution of non-interacting magnetite NPs.…”
Section: Resultssupporting
confidence: 90%
“…The M s value is in agreement with the measured value whereas the K eff value is in good agreement with the reported value for bulk magnetite29. Differences between the experimental and calculated FC curves could be assigned to the occurrence of particle-particle interaction, once the effect of those interactions is the flattening of the FC curves, in agreement with the literature30. In the low temperature region the blocking temperature distribution has been assigned mainly to the contribution of non-interacting magnetite NPs.…”
Section: Resultssupporting
confidence: 90%
“…Physically, these extra features cannot fully be due to the interaction fields, but they have been previously shown to be potentially from thermal fluctuations [51]. Other magnetic measurements, such as ferromagnetic resonance, have shown that interaction fields cause broadening and/or shifts of the P Hc peak [52][53][54][55], but not necessary inducing extra local minima/maxima. Similar problems arise with P Hu distributions in figure 5.…”
Section: Resultsmentioning
confidence: 98%
“…Herein, exchange coupling is neglected and long-range dipolar interaction is taken into consideration. 21,22 For an ensemble of randomly distributed NPs, this energy barrier is thus revised by the mean-field approximation: 23,24 …”
Section: Sarmentioning
confidence: 99%